Assessment Of Natural Radionuclides Activity And Heavy Metals Concentration In Paddy Plants And Their Influencing Factors In Penang, Malaysia - Al-Saffar, Mohammed Saad (2017)
This research focus on the measurement of natural radioactivity and heavy metals in rice (Oryza sativa) and its surrounding media, which include agriculture soil and irrigation water. In order to determine the absorption of these metals by rice, the usage of fertilizers and the physico-chemical features of soil, such as pH, cation exchange capacity, electrical conductivity, organic matter, and soil texture were also studied. Rice and soil samples were acquired from 23 different areas in Penang, and the water specimens were retrieved from the main rivers of the study area. Laboratory studies were performed on 3 common fertilizers and uptake of 226Ra, 232Th and 40K by rice grain using potted plants at 3 growth stages.